Animal farm - Orwell, George (Heinemann, 1954)
Unhappy with the poor living conditions they must endure, the animals of Manor Farm gather for a secret meeting to plan a revolt. The animals fight and win their freedom, naming their newly claimed property Animal Farm. All seems perfect, until the desire for power and other traits they had despised in their original owner show through in the animals now running the farm. Life is not what they had hoped it would be.